Advancing Women's Leadership in Cultivating a Quality Culture in Indonesian Vocational High Schools: An Islamic Educational Perspective - Siswadi, Siswadi; Zain, Muhammad Fuad; Roqib, Moh.; Masruri, Muhammad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This research examines the transformative role of female leadership in fostering a culture of quality in Vocational High Schools (SMK) in Indonesia from the perspective of Islamic education, guided by Islamic educational values and ethics. Using a qualitative, phenomenological approach, this study examines how female principals serve as agents of change in the vocational education landscape. Data were collected through in-depth interviews, observation, and document analysis. In-depth interviews were conducted with female principals as part of expert triangulation to enrich perspectives on Islamic education and the transformation of women's leadership. The interviews were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research revealed five strategic approaches used by women leaders: transitioning from top-down to participatory decision-making; recognising teachers as internal clients to enhance collaboration; benchmarking with high-performing schools to set quality standards; improving infrastructure to meet national benchmarks; and building partnerships with industry to ensure graduates' relevance in the labour market. The novelty of this research lies in integrating Islamic leadership principles with contemporary quality management, which offers a gender-inclusive framework. The findings provide valuable insights into how women's leadership drives sustainable vocational education reforms that align with the needs of leaders in the workforce.